Risk factors in relation to human deaths and other tsunami (2004) impacts in Sri Lanka: the fishers'-eye view - Venkatachalam, A.J.; Price, A.R.G.; Chandrasekara, S.; Senaratna Sellamuttu, Sonali (Wiley, 2009)
This study examines the perceptions of 500 Sri Lankan fishers about influences on the outcome of the 2004 Asian tsunami. It is based upon analysis of questionnaire data on 13 natural environmental and development risk factors, in relation to human deaths and house damage (impact indicators). Mangroves, coral reefs and sand dunes afforded protection against tsunami damage (67-94% of fisher responses), as did housing and roads. Fishers overall believed rivers/estuaries, concave coastlines and hotels exacerbated impacts. However, a significantly greater proportion of fishers living within 100m of the coast reported that rivers/estuaries had a protective role than those living further inland. Rivers seemingly diverted 'tsunami water' far inland, where it overflowed and caused damage. Risk and damage are multi-faceted concepts and measurable in different ways. Findings are considered in the light of ecological studies and modelling, with special reference to mangroves, whose alleged protective role has become equivocal during post-tsunami research. Insights of fishers and other communities with intuitive knowledge add a valuable perspective to the understanding of natural disasters and environmental change. This approach is seen as complementary rather than an alternative approach to purely 'scientific' research.